2015
DOI: 10.1111/vco.12130
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the cytotoxic effect of flavopiridol in canine lymphoma cell lines

Abstract: The cyclin-dependent kinase (CDK) inhibitor, flavopiridol, was tested as a potential new cancer therapeutic agent to treat canine lymphoma by examining its effect on cell growth of canine lymphoma cell lines in vitro. Flavopiridol induced profound cell death in all eight lymphoma cell lines at 400 nM, and in all cases cell death was due to apoptosis. Apoptosis was inhibited by caspase inhibitor, despite the variable sensitivities between cell lines. Analysis of the mechanism of flavopiridol-induced apoptosis s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The possibility of using of FVP in veterinary oncology has also been explored. It was demonstrated that FVP at a concentration of 400 nM was able to induced apoptosis in many different canine lymphoma cell lines (CLBL-1, Ema, CL-1, GL-1, UL-1, CLGL90, Nody-1 and 17-71) (41). Accordingly, we found that CLBL-1 cells showed a remarkable sensitivity to FVP-induced cell death, being able to induce about 70% of dead cells after 24 h exposure at 200 nM, and around 30% when used at 100 nM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possibility of using of FVP in veterinary oncology has also been explored. It was demonstrated that FVP at a concentration of 400 nM was able to induced apoptosis in many different canine lymphoma cell lines (CLBL-1, Ema, CL-1, GL-1, UL-1, CLGL90, Nody-1 and 17-71) (41). Accordingly, we found that CLBL-1 cells showed a remarkable sensitivity to FVP-induced cell death, being able to induce about 70% of dead cells after 24 h exposure at 200 nM, and around 30% when used at 100 nM.…”
Section: Discussionmentioning
confidence: 99%
“…Although the antitumor activity of FVP alone has already been explored in dogs (41), to our knowledge the combination of TRAIL with FVP has not yet been analyzed in canine tumors. Hence, we decided to examine the TRAILsensitizing activity of the aforementioned compound in canine lymphoma.…”
mentioning
confidence: 99%